ANALYSIS OF SOLID WASTE MANAGEMENT GENERATED BY LAYING HENS ON A FAMILY FARM - Lima, P. G.; Braga, W. R. O.; Lourenzani, A. E. B. S.; Forti, J. C. (Revista Brasileira de Engenharia de Biossistemas, 2016)
As part of the agricultural activity, egg production generates solid waste that, if left untreated, can lead to significant environmental problems such as contamination of soil and groundwater. The aim of this paper is to analyze the solid waste management generated by a family farm located in northwest São Paulo, in order to verify if the practices used are based on current environmental legislation, more specifically, on National Policy for Solid Waste. . The following question is proposed: How is the management of solid waste generated by laying hens on a family farm? For this purpose, a case study of exploratory-descriptive character was carried out, with a qualitative approach in data collection, using semi-structures formulary ad interviews with the owner. As a result, it was possible to observe that the farm, although received guidance on the appropriate way of allocating its waste, has not yet incorporated them as a conscious process of environmental preservation, making adequate destination only when it presents itself as a threat of monetary punishment.